(untitled) (Journal of Digital System Development, 2024)
Library usage refers to how users interact with library resources and spaces, including borrowing books, reserving study rooms, navigating library spaces, and using digital resources. Analysing library usage patterns helps libraries optimise resources, improve services, and better meet the needs of their users. This study aims to visually explore the patterns in book loan activities and room reservation behaviours using the R programming language to identify trends that provide preliminary data for decision-making when establishing library operational policies. Annual book loan and room reservation data from 2017 to 2023 from Perpustakaan Sultanah Bahiyah, Library of Universiti Utara Malaysia, were collected and converted into a compatible R-analysis format. The analysis includes exploratory data analysis and visualisation using base R functions, base R graphics, and ggplot2 functionality. The findings, such as annual book loan rates, trends in book loan rates between undergraduate and postgraduate students, frequency of room reservation discussions across years, and the relationship between book loans and room reservations over time, serve as foundational data to support decision-making for the efficient operation of libraries and to inform strategies for optimising library services and resources to meet user needs better.